T6 Impact Of Environmental Differences In The Prevalence Of Airway Dysfunction In Elite Athletes: Gb Boxing Vs. Gb Swimming. (10th November 2014) - Levai, IK; Dickinson, JW; Loosemore, M; Greenwell, J; Hull, JH; Whyte, G
Abstract : Objectives: Exercising in a provocative environment (e.g. indoor swimming pool) at sustained high minute ventilation rates may increase the prevalence of airway dysfunction in athletic populations. The purpose of the study was to evaluate the impact of environmental differences in the prevalence of airway dysfunction in two cohorts of elite GB athletes. Methods: Airway dysfunction was evaluated in the GB boxing (n = 39, Mean (SD) age: 22.0 (3.2) yrs.) and swimming squads (n = 33, Mean (SD) age: 21.0 (3.0) yrs.). All participants completed a Eucapnic Voluntary Hyperpnoea (EVH) challenge test, an indirect bronchoprovocation test, to characterise airway dysfunction (defined as abnormal if >10% fall in FEV1 post-challenge). Fraction of exhaled Nitric Oxide (FeNO) was measured and participants completed a symptom and medication questionnaire. Results: The prevalence of airway dysfunction was greater in elite swimmers (70%) than boxers (8%) (p < 0.001) (Figure 1 ). The EVH assessment process revealed missed and incorrect diagnosis of airway dysfunction; specifically 65% (17 of 26) of those with airway dysfunction had no prior diagnosis of asthma or exercise induced bronchoconstriction. Moreover, a prior diagnosis of asthma was not supported by testing in 9% (4 of 46) of the athletes. These athletes were prescribed one or a combination of short-acting β2-agonists, long-acting β2-agonists and inhaled corticosteroids. Neither symptoms nor baseline lung function were predictive of a positive EVH-challenge in swimmers. No correlation between change in lung function or airway dysfunction and FeNO value. Conclusions: The prevalence of airway dysfunction was nine fold greater in elite swimmers when compared with boxers. This finding emphasises the high proportion of EVH-positive elite swimmers and the importance of strategies needed to ensure their respiratory health is optimised. These results also suggest that airway dysfunction is not only related to intensity and frequency of exertional hyperpnoea but also environmental conditions.